Dominant Factors Level of Safety Culture Maturity Model With Work Accidents at PT Barata Indonesia - Juwita, Luthfiyah Purnama; Dwi Pasca Budiono, Nugrahadi (Universitas Muhammadiyah Palu, 2024)
Background: Many work accidents are caused by worker carelessness and work environment is an indicator of work safety culture maturity model. Objective: To analyze the dominant factors that effect the level of safety culture maturity model at PT Barata Indonesia. Method: The research design is a cross sectional survey with an observational approach. The population is all workers in 2023 as many 625 people. Total sample of 244 respondents was taken using simple random sampling. Independent variables: commitment, leadership, responsibility, competence, involvement, information and communication, risk, and organizational learning, while the dependent variable is work accidents. Instruments used were a questionnaire sheet regarding the safety culture maturity model and work accident history form. Statistic test using Chi-Square test and Logistic Regression. Results: The overall level of safety culture maturity model is at a proactive level with the majority of work accidents never occurring (58.6%). Chi-Square test and Logistic Regression test result a value of p = 0.000 < 0.05, with the risk variable having the highest Exp(B) value (3.187) compared to other variables. Conclusion: There is an effect on the level of safety culture maturity model on work accidents, and risk is the most dominant factors. Discussions about safety can strengthen practices that minimize the occurrence of work accidents, as well as ensuring cultural safety in operations and work.